The role of energy subsidy reform in energy efficiency enhancement: Lessons learnt and future potential for Iranian industries. (1st October 2018) - Barkhordar, Zahra A.; Fakouriyan, Samaneh; Sheykhha, Siamak
Abstract: Significant energy subsidies are believed to be the main factor that has resulted in high energy intensities of Iranian industries. The Subsidy Reform Act of 2010 was directed at modifying energy consumption pattern and fostering energy efficiency enhancement. This study aims at analyzing the effect of energy subsidy reform on promoting energy efficiency in six energy intensive industries of Iran. In order to do so, the energy efficiency practices that have not been adopted after the implementation of the first phase of energy subsidy reform are investigated. Data analysis reveals that if financially interesting investments are determined as those with payback periods less than three years, there exist more than 80 PJ energy saving potential that have not been realized yet. The large amount of missed energy savings demonstrates that before complete energy subsidy removal, barriers that discourage investors from moving forward with energy efficiency projects should be removed. These barriers can be classified as informational barriers, financial barriers and administrative and regulatory barriers. Inspired from product life cycle, a sequential strategy is proposed to strengthen the positive impacts of increasing energy prices and to weaken the negative effects of barriers. The strategy is composed of an introductory stage in which deployment of energy efficiency solutions starts to grow without further increasing energy prices; a growth stage when viable and interesting energy efficiency solutions are adopted and then the efficiency market becomes mature. Next phases of energy subsidy reform can be implemented at this stage. Graphical abstract: Highlights: Subsidies Reform Act was directed at fostering energy efficiency enhancement. Large amount of missed viable energy savings even after energy subsidy reform. Informational, financial and regulatory barriers impeded energy efficiency practices. A sequential strategy is proposed to boost efficiency increase.